PEMBUATAN SERTA KARAKTERISTIK BATAKO MENGGUNAKAN BATU APUNG DAN LIMBAH PADAT BENANG KARET DENGAN PEREKAT RESIN EPOKSI - nia nenshi siregar (Saintia Fisika, 2013)
The study of manufacturing and characterizing of concrete block using pumice, solid waste rubber thread with resin epoxy as binder material had been dane. Variation of compositions made in this research, including percentage that is amount of waste rubber : 0, 2, 4, and 6% of the total used pumice and epoxy resin : 20, 25, and 30% weight of the total aggregate. The physical and mechanical magnitude which are measured that are : water absorbtion, porosity, impact, flexural strength. The addition of pumice relatively degrades the physical and mechanical properties of concrete block. Conversely, if the amount of epoxy resin increased, hance quality of concrete block tend to increase also. Through the testing, the resulted output sample had characteristics : water absorption = 0.90%, porosity = 1%, Impact = 0.90 kJ/m2 and flexural strength = 35.22 MPa. Keywords : concrete block, pumice, waste rubber, epoxy resin